2013
DOI: 10.1097/jto.0b013e31829ce93e
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Analysis of EGFR and KRAS Mutations in EUS and EBUS-Derived Cytologic Samples of Adenocarcinomas of the Lung

Abstract: Pyrosequencing on cytological blocks, especially older tumor blocks, is feasible with a high diagnostic success rate. Failures in HRM were observed in DNA samples with short fragments related to longer storage times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…Several groups have shown the retrospective analysis of fixed EBUS-TBNA samples can be used to identify clinically actionable mutations in lung cancer [29][33], and that high quality DNA, RNA and protein can be obtained from these samples [34], [35]. Our data extend these studies by demonstrating that freshly isolated EBUS-TBNA samples can generate high-quality DNA suitable for massively parallel targeted re-sequencing that avoids formalin artefact, and that can be carefully controlled for stromal artefact.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown the retrospective analysis of fixed EBUS-TBNA samples can be used to identify clinically actionable mutations in lung cancer [29][33], and that high quality DNA, RNA and protein can be obtained from these samples [34], [35]. Our data extend these studies by demonstrating that freshly isolated EBUS-TBNA samples can generate high-quality DNA suitable for massively parallel targeted re-sequencing that avoids formalin artefact, and that can be carefully controlled for stromal artefact.…”
Section: Discussionmentioning
confidence: 99%
“…68 Cell blocks have been shown to be comparable to core biopsies in some studies for detection of clinically important mutations. 3,69 A significant number of studies have shown that smears and CBs are equivalent for molecular testing. 66,7072 In an analysis of 181 articles focusing on EGFR analysis in lung cancer, da Cunha Santos et al 64 showed that cytologic techniques using an array of fixation and processing techniques yielded mutation detection rates similar if not superior to histologic material.…”
Section: Committee IVmentioning
confidence: 99%
“…3,6569 While FFPE material is one of the most common sources of material for molecular analysis in many laboratories, 67, 72 recent studies have shown that material obtained from air-dried and alcohol-fixed cytologic smears can be reliably used. 61,62,73,74 Sample adequacy for analysis should be confirmed by a pathologist.…”
Section: Committee IVmentioning
confidence: 99%
“…Of the remaining 140 patients, 85% had sufficient material for EGFR and kras testing (12 had no DNA, 4 had unsuccessful amplifications, and 5 had insufficient DNA). 40 …”
Section: Endobronchial Ultrasound Bronchoscopymentioning
confidence: 97%